The Impact of Divorce on Children According to a Review of Islamic Law - Widiastuti, Indriani (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2021)
In this journal, the author discusses the impact of divorce on children according to a review of Islamic law, Divorce is a break in the marital bond between the two parties, namely husband and wife due to the occurrence of a fractured family relationship disharmony on the basis of an internal factor or an external factor that occurs. As in the case of divorce, which often ends at the court, the divorce that occurs will of course also have legal consequences for husband and wife, children and joint property. In the family, religion and education are very important so that life in the household can be harmonious and there are fewer divorce cases, and can provide understanding so that parents who want to divorce can find out in more detail or better understand what impacts can happen to children, not only the impact but the law in divorce is also discussed in this journal, not a few are currently experiencing divorce and most of them already have children and in this problem will be studied using research methods with a qualitative approach, namely a research process and understanding based on methodology that investigates a social phenomenon and human problem.